BIOREMEDIASI LIMBAH RUMAH TANGGA DENGAN SISTEM SIMULASI TANAMAN AIR - Guntur Yusuf (Environmental Research Center (PPLH) of Udayana University, 2008)
This research was aimed to find out the influence of bioremediation with simulation on some compositions to increase the quality of treated domestic wastewater, to describe the role of aquatic plant compositions, and to measure the effectiveness of each aquatic plant in reducing levels of pollutants. Laboratory tests were performed to recognize the waste quality, including physical, chemical and microbiological qualities, after bioremediation processes. Bioremediation process obviously had significant effects on the increase of treated domestic wastewater quality. Aquatic plant compositions and dilution factors were obviously interacting in increasing the quality of treated domestic wastewater. The composition of aquatic plants provided distinctive effects. Each kind of aquatic plant provided a specific effect on the increase of the domestic wastewater quality in various percentages.